Wireless power and data transfer through carbon composite using a common inductive link - Tuan Anh Vu; Chi Van Pham; William Tran; Anh-Vu Pham; Christopher S. Gardner (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This paper presents the design and development of an integrated wireless power transfer and data communication system. The power and data transfer share a common inductive link that consists of two identical Helical coils placed on both sides of a carbon composite barrier. Power and data are transferred simultaneously through a 5-mm thick carbon composite barrier without any physical penetration or contact. Power transfer measurements show that the system can deliver 9.7 AC power to the receiving coil with a power transfer efficiency of 36% through the carbon composite barrier. The system achieves a bidirectional half-duplex data communication with the data rate of unit 1.2kbit/s.